Chemical, physical and physiological quality attributes of fruit and vegetables induced by cold plasma treatment: Mechanisms and application advances. Issue 16 (7th September 2020) - Chen, Ya-Qi; Cheng, Jun-Hu; Sun, Da-Wen
Abstract: In recent years, applications of cold plasma treatments have shown high efficiency in sterilization of fresh fruit and vegetables. With encouraging results, development of this technique focuses on influences of cold plasma on the quality attributes of these fresh produce. More studies found that the quality attributes are maintained in an acceptable range or can even be improved under certain plasma treatment conditions. This review provides an overview of the multiple effects of cold plasma on the fresh produce, in terms of physical, chemical and physiological aspects. Besides, the possible mechanisms of how plasma influences these quality attributes is elaborated, which is useful for further modification and improvement of the plasma technology, so that quality enhancement and shelf life extension can be achieved. Future trends in the development of cold plasma technology are also presented. Cold plasma treatment is a potential technology for treating fresh fruit and vegetables to enhance their quality and extend their shelf life. However, knowledge of the effects of cold plasma on the quality changes of fresh fruit and vegetables is still limited. Therefore, there is a need for future studies to understand the mechanisms of plasma effects on controlling the interactions between plasma and food products in order to realize the early adoption of the technology to the food industry.